Kader Posyandu sebagai Agen Pencegahan Primer Tindakan Kekerasan Seksual pada Anak - Anisa Fariani; Ira Paramastri (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2015)
This study aimed to examine the effect of child sexual abuse  (CSA) prevention training  toward  the  knowledge  and  examine  the  effect of health promotion program using lecture and leaflet conducted by cadre applied in community. The method used was a quasi experimental study using the one group pretest-posttest design and untreated control group design with dependent pretest-posttest samples. There were 19 cadres involved in this study. Questionnaires on knowledge, observation, and interview were used in this study. Repeated measures  anova  and  mixed  anova  were  used  to analyse the  quantitative  data,  descriptive analyse was used to analyse data from observation and interview. Data analyse was used to identify  differences of  knowledge before-after CSA prevention training and to examine  the effect  of  lecture and leaflet toward improvement of community knowledge. The results showed there was a significant difference in knowledge before and after training (F=20.245, p<0.05). Lecture and leaflet was effective to increase knowledge about CSA (F=3.379, p<0.05). Leafletwas more effective to  increase  knowledge  (MD=-2.824; p<0.01)  than  lecture  (MD=-2.355; p<0.01).